2020
DOI: 10.1007/s12035-020-01875-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pro-cognitive and Neurochemical Profiles of Glycine Modulatory Site Agonists and Glycine Reuptake Inhibitors in the Rat: Potential Relevance to Cognitive Dysfunction and Its Management

Abstract: Frontocortical NMDA receptors are pivotal in regulating cognition and mood, are hypofunctional in schizophrenia, and may contribute to autistic spectrum disorders. Despite extensive interest in agents potentiating activity at the co-agonist glycine modulatory site, few comparative functional studies exist. This study systematically compared the actions of the glycine reuptake inhibitors, sarcosine (40-200 mg/kg) and ORG24598 (0.63-5 mg/kg), the agonists, glycine (40-800 mg/kg), and D-serine (10-160 mg/kg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 121 publications
(196 reference statements)
1
7
0
Order By: Relevance
“…The present study may also offer a cellular explanation for previous studies showing that D-serine plays a major role in cocaine-induced sensitization (45,46) and to studies suggesting that the novel antipsychotics cariprazine and blonaneserin strengthen cognitive functions by virtue of their attenuation of D3R activity in the PFC (47,48). In addition, there is increasing interest in the potential utility for ligands at NMDAR in the management of other disorders from autism to Alzheimer's disease (49,50).…”
Section: Discussionsupporting
confidence: 64%
“…The present study may also offer a cellular explanation for previous studies showing that D-serine plays a major role in cocaine-induced sensitization (45,46) and to studies suggesting that the novel antipsychotics cariprazine and blonaneserin strengthen cognitive functions by virtue of their attenuation of D3R activity in the PFC (47,48). In addition, there is increasing interest in the potential utility for ligands at NMDAR in the management of other disorders from autism to Alzheimer's disease (49,50).…”
Section: Discussionsupporting
confidence: 64%
“…These types of drugs include glycine itself [ 145 , 146 , 147 ], other agonists of the NMDA-glycine recognition site such as D-serine [ 148 , 149 , 150 ] and the partial agonist D-cycloserine [ 151 , 152 , 153 , 154 , 155 ], as well as inhibitors of glycine transporters, such as sarcosine ( N -methyl-glycine), which increase the synaptic availability of glycine [ 156 , 157 ]. However, although preclinical studies in rodents showed that partial glycine site agonists and glycine reuptake inhibitors exhibit comparable pro-cognitive effects with the potential for the treatment of schizophrenia [ 158 ], a double-blind, randomized clinical trial concluded that neither glycine nor D-cycloserine is a generally effective therapeutic option for treating negative symptoms or cognitive impairments [ 147 ]. As a matter of fact, most clinical trials conducted to date have failed to show efficacy of these agents for the treatment of schizophrenia [ 159 ].…”
Section: Nmda Receptors As Target For Treatment In Schizophreniamentioning
confidence: 99%
“…Therefore, in addition to the long-established “glycine neurophysiology” via (1) binding sites on glutamate NMDA receptors 56 , and (2) its cognate receptors (GlyR) in subtelencephalic areas 57 , our findings point to the third type of mechanism, starting with tRNA Gly epitranscriptomic modification, by which glycinergic pathways could critically regulate adult brain function and complex behaviors. Pharmacological alterations in glycine function in the brain 58 have shown promise for alleviating cognitive deficits 59 and depressive symptoms in humans 60 and animal models 61 , 62 . The findings presented here broadly align with the therapeutic promise of glycinergic pathways.…”
Section: Discussionmentioning
confidence: 99%